Reconciling independence and accountability in judicial systems - Francesco Contini; Richard Mohr (Utrecht Law Review, 2008)
The article analyses recent European experience in applying new managerial mechanisms of accountability to justice systems. A common outcome has been a confrontation between demands for accountability faced with appeals to judicial independence. We analyse the traditional forms of legal (or judicial) and managerial accountability, identifying the source of the values on which each is based, and the consequences of each. This highlights the different epistemic orientation: the legal system deals with individual cases and the proper application of the law, the managerial system with aggregate of activity, outputs, and expenditure. To overcome the stalemate that so often results, we review the concept of accountability, drawing attention to the breadth of values and interests to which courts must respond. We further note that independence is not an end in itself, but must be appreciated instead as the guarantee of judicial impartiality. We are then in a position to compare different European case studies of implementation of new mechanisms of accountability with the goals and values of the justice system. Poor efforts are typically ritualistic zero-sum games, devoting increasing amounts of energy to measurement while losing sight of why anything is being measured. Successful review mechanisms bring together various interested parties to identify important outcomes that are readily measurable and capable of improvement.